How Reliable Are Social Safety Nets in Situations of Acute Economic Need? Extended Estimates for 14 OECD Countries - Raphaela Hyee; Herwig Immervoll; Rodrigo Fernandez; Jongmi Lee; Karl Handscomb (Institute of Labor Economics (IZA), 2024)
We present an empirical assessment of the accessibility and levels of 'safety-net' benefits. Complementing existing studies, which often adopt an institutional focus or compare legal entitlement rules, it employs a people-centred perspective, using data on cash support that people receive in practice. The approach is illustrated by comparing minimum-income benefits (MIB) and other non-contributory transfers across 14 OECD countries in Asia, Europe, North America and Oceania. Accessibility differs widely across countries and family circumstances. When out of work and in the bottom income decile, more than 4 out of 5 single-person households reported receiving MIB in Australia, France, and the United Kingdom, compared to 1 in 3 in Italy. In some countries, even very low earnings made benefit receipt unlikely, weakening financial work incentives. Typical benefit payouts to low-income claimants amounted to 15% of median household incomes or less in Greece, Korea, and the United States, but exceeded 40% in Belgium and the United Kingdom. Support from non-contributory transfers varied across groups, with countries variously focusing support on people with health problems (Italy) or on families with children (Germany, Greece, United States).
Keywords: H53; H31; D31; I38; C31; C53; 330; adequacy; non-take-up; accessibility; coverage; minimum-income benefits; poverty